Model for Investigation of Operational Wind Power Plant Regimes with Doubly–Fed Asynchronous Machine in Power System - R. I. Mustafayev; L. G. Hasanova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper presents methodology for mathematical modeling of power system (its part) when jointly operated with wind power plants (stations) that contain asynchronous doubly-fed machines used as generators. The essence and advantage of the methodology is that it allows efficiently to mate equations of doubly-fed asynchronous machines, written in the axes that rotate with the machine rotor speed with the equations of external electric power system, written in synchronously rotating axes.